Indigenous Entrepreneurship and Economic Development: The Moderating Effect of Post-Conflict Reconstruction in Turkana County, Kenya - Wambui King’ong’o; Martin Ogutu; Samuel Nyandemo (European Scientific Journal, ESJ, 2020)
The role of entrepreneurship in post-conflict reconstruction is largely understudied. Micro and Small livestock enterprises play an important economic and socio-cultural role amongst many Kenyan communities. The objective of this study was to establish the moderating effect of post-conflict reconstruction on the relationship between indigenous entrepreneurship and economic development in Turkana County. This study is anchored on institutional theory. Positivism and phenomenology paradigms and a cross sectional research design was adopted. The target population was all micro and small livestock enterprises that are registered members of the Livestock Marketing Association (LMA) in Turkana County; comprising of 598 livestock enterprises. A sample of 339 micro and small livestock enterprises were selected for the study using simple random sampling techniques. Data collected were analyzed using descriptive and inferential statistics like mean, standard deviation, cumulative variance, Skewness, Kurtosis, ANOVA and regression analyses. The results revealed that Post-conflict reconstruction has a significant moderating effect on the relationship between indigenous entrepreneurship and economic development in Turkana county, (F=50.22, P=0.000). The study suggests legislation of laws and policies by the national and County governments, prohibiting acquisition of small arms. Policy initiatives should support indigenous livestock enterprises for instance, creation of a suitable environment for these businessesto obtain credit. Itstime both levels of governments enhance their environmental factors to lower uncertainty, raise indigenous livestock entrepreneurs to participate at the global economy, attracting FDI, private sector development, employment, increased exports and finally spur economic development through huge investments in health, education while impacting wealth levels.